Lateral dynamic load tests of offshore piles based using the m-method. (15th January 2021) - Wang, Jin-Peng; Su, Jing-Bo; Wu, Feng; Zhang, Zheng; Lv, Yaru
Abstract: The static load test method is currently the standard horizontal bearing capacity test for offshore foundation piles. The static load test method requires extensive testing time, high equipment cost, and uses equipment sensitive to environmental conditions. As offshore wind power piles increase in diameter, the static load test method becomes increasingly cumbersome to use. In this contribution, a single pile model test under the action of static force and impact was carried out. Based on the m-method, the dynamic and static transformation relationship of m value in the test was explored, and a new lateral dynamic load test method for offshore piles is proposed. The new method employs the in-situ ship impact impulse test method. The m-value dynamic-static ratio (m value under dynamic force/m value under static force) exhibits a quadratic parabolic distribution relative to horizontal displacement and external load. The m value under impact can be converted into the equivalent static m value, which can be used to analyze the pile-soil interaction and evaluate the pile horizontal bearing capacity. Highlights: The dynamic test suitable for evaluating the carrying capacity than static test. A dynamic test method targeting at m-value feasible in the field test evaluation. Equivalent static load-displacement curve obtained by pulse equivalent method. Dynamic-static ratio of m value parabolic with mud surface displacement.